Modeling the extra pass in basketball - Supola, B.; Hoch, T.; Baca, A. (13th World Congress of Performance Analysis of Sport and 13th International Symposium on Computer Science in Sport. IACSS&ISPAS 2022, 2023)
The ability to make the extra pass is held to be one of the most crucial skills for creating better ball movement - and by that more efficient teamwork. However, judging this skill is completely left to the subjectivity of the coaches, as at this moment there is no metric to assess player performance in this regard. Using positional data from the SportVU data set, we propose a method to analyze game situations where an extra pass would lead to a shooting opportunity with higher expected points than the direct shot. Evaluating these situations provides experts the possibility to assess team intelligence on player level.